Development of an immunomodulatory biomaterial: Using resolvin D1 to modulate inflammation. (June 2015) - Vasconcelos, Daniela P.; Costa, Madalena; Amaral, Isabel F.; Barbosa, Mário A.; Águas, Artur P.; Barbosa, Judite N.
Abstract: In our search for immunomodulatory biomaterials capable of modulating the inflammatory response through M2 macrophage polarization, we report here on a new strategy that resulted from the incorporation of resolvin D1 (RvD1), a pro-resolution lipid mediator in porous 3D chitosan (Ch) scaffolds, followed by its lyophilisation. We have investigated the inflammatory response caused by this biomaterial in vivo using a mouse air-pouch model of inflammation. We found that this developed material caused a decrease in inflammatory cells recruited to the implant site, together with higher numbers of F4/80 + /CD206 + cells (M2 macrophages) and lower numbers of F4/80 + /CCR7 + cells (M1 macrophages). It also induced a general decrease in pro-inflammatory cytokines, and caused a decrease in the inflammatory cells observed around and within the implanted scaffolds, when compared with Ch alone or Ch not submitted to lyophilisation after RvD1 incorporation. Our results demonstrate that we were able to develop an immunomodulating biomaterial that triggers a shift in the macrophage response towards a M2 reparative response that will be advantageous for the host.